Study of ionization equilibrium taking into account the depression of ionization potential in a dense degenerate plasma - Shalenov Е.О.; Zhumasheva С.Р.; Seitkozhanov E.С.; Dzhumagulova К.Н. (Recent Contributions to Physics, 2024)
In modern plasma research, special attention is paid to the study of ionization equilibrium under conditions of dense degenerate plasma, especially taking into account the depression of ionization potential. In this work, we conducted a study of this phenomenon in order to identify the main patterns and mechanisms that determine the state of dense plasma. The goal of the study is to analyze the effect of depression of ionization potential on the ionization equilibrium in a dense degenerate plasma. We propose a new approach to describe this phenomenon that takes into account both the Debye and Thomas-Fermi screening lengths. This work has both scientific and practical significance. From a scientific point of view, it expands our understanding of plasma physics under extreme conditions, which has important implications for various fields of physics, including astrophysics and laser plasmadynamics. From a practical point of view, the results of the study can be useful for the development of new methods for controlling plasma processes in various technological applications, such as inertial thermonuclear fusion and thermonuclear ignition. The research methodology includes mathematical modeling and numerical calculations based on the Saha equations, which take into account the depression of ionization potential. The main results of the work suggest that the depression of ionization potential leads to significant changes in the ionization equilibrium in a dense plasma. Overall, this study makes a significant contribution to the field of plasma physics by providing new knowledge about the behavior of dense degenerate plasmas taking into account the depression of ionization potential.